PENGUATAN MODERASI BERAGAMA MELALUI PERAN GURU PAI DAN BUDI PEKERTI DI SMK YADIKA BANDAR LAMPUNG - Dimas Raba Pramodana; Chairul Anwar; Eti Hadiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia, as a country with a high level of religious and cultural diversity, requires strengthening the value of religious moderation in education. Islamic Religious Education and Character Education teachers have a strategic role in instilling moderate, tolerant, and inclusive religious attitudes in students. This study aims to analyze the role of Islamic Religious Education and Character Education teachers in strengthening religious moderation in students at SMK Yadika Bandar Lampung, including the forms of their roles, the strategies implemented, and the supporting and inhibiting factors. This study uses a qualitative approach with a case study research type. Data collection techniques were carried out through observation, in-depth interviews, and documentation with the principal, vice principal for curriculum, Islamic Religious Education and Character Education teachers, interfaith teachers, and students. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, with data validity checks using triangulation. The results of the study indicate that Islamic Religious Education and Character Education teachers play a role as educators, role models, facilitators, motivators, and mediators between religious communities in instilling the values ​​of religious moderation. The strategies used include integrating the value of moderation into learning, modeling attitudes, fostering tolerant behavior, and inclusive religious and social activities. Supporting factors come from inclusive school policies and teacher commitment, while inhibiting factors include limited learning time and the influence of students' external environment. This study confirms that the role of Islamic Religious Education and Character Education teachers contributes significantly to strengthening students' moderate attitudes in multicultural school environments.